Some hyperstability results of a p-radical functional equation related to quartic mappings in non-Archimedean Banach spaces - Nuino,Ahmed (Universidad Católica del Norte, Departamento de Matemáticas, 2021)
Abstract The aim of this paper is to introduce and solve the following p-radical functional equation related to quartic mappings where f is a mapping from R into a vector space X and p ≥ 3 is an odd natural number. Using an analogue version of Brzdȩk’s fixed point theorem [13], we establish some hyperstability results for the considered equation in non-Archimedean Banach spaces. Also, we give some hyperstability results for the inhomogeneous p-radical functional equation related to quartic mapping.